IMPLEMENTASI KEBIJAKAN BANTUAN STUDI LANJUT BAGI DOSEN PADA PERGURUAN TINGGI NEGERI BERBADAN HUKUM (STUDI KASUS UNIVERSITAS DIPONEGORO) - Muhammad Haris Zakiyuddin; Kismartini Kismartini; Amni Zarkasyi Rahman (Journal of Public Policy and Management Review, 2023)
Undip as one of the PTN-BH must have quality human resources to be able to provide quality educational services. Looking at Undip's resources, the number of lecturers with PhD/Sp-2 qualifications in 2021 did not reach the target. Apart from that, the number of lecturers holding doctoral degrees in 2017, 2018 and 2021 did not reach the stated target. Undip itself has a further study assistance policy. However, in its progress there are few people interested in further study assistance programs for lecturers. This research use desciptive qualitative approach. The research aims to analyze policy implementation and identify supports and obstacles in implementation. The research results show that the implementation of the current study assistance policy is good. This is seen from the policy output, the target group's willingness to comply with the policy output, as well as the actual impact of the policy output. This research also shows that there are supporting factors for policy implementation consisting of financial allocation, formal access from outside parties, public support, as well as the commitment and ability of implementing officials. Meanwhile, the factors inhibiting the implementation of this policy are clarity of policy content as well as social, economic and technological conditions.